Constructing a Sensitizing Definition of Certification in Nursing for Research Purposes: A Hybrid Methodology Using Consensus-Building Approach. (January 2019) - Chappell, Kathy; Jeong, Dahn; ElChamaa, Rima; Lundmark, Vicki; Kendall-Gallagher, Deborah; Salt, Elizabeth; Newhouse, Robin; Johantgen, Meg; Reeves, Scott; Moore, Donald; Olson, Curtis; Van Hoof, Thomas; et al.
Abstract : OBJECTIVE: The aim of this study was to construct a sensitizing definition of certification in nursing for research purposes that can provide a foundation from which to further develop a coherent research program building evidence about the impact of certification on healthcare outcomes. BACKGROUND: The lack of a single definition of certification in nursing makes it difficult to draw conclusions about the relationship between specialty certification and patient outcomes. METHODS: This study was guided by the Delphi-Chaffee hybrid methodology proposed by Grant et al. DISCUSSION: Constructing a single, sensitizing definition of certification: 1) provides coherency for direction of certification research; 2) serves as a guide for researchers; and 3) facilitates multimethodological approaches to exploring the relationship among the different components of the definition of certification. CONCLUSION: A sensitizing definition of certification provides an opportunity for researchers to study the relationship between nursing certification and patient outcomes.